High-impact fluorine-free halogen-free flame-retardant polycarbonate composition as well as preparation method and application thereof

By using fluorine-free, halogen-free polycarbonate flame retardant masterbatches and specific copolymers in polycarbonate materials, the flame retardancy and mechanical properties of the material are improved, and the problem of insufficient flame retardant performance of existing polycarbonate materials is solved. And avoid the risk of policy restrictions due to fluorine or halogen.

CN119505506APending Publication Date: 2025-02-25CHONGQING ORINKO TECH CO LTD CHINA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411651595.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing polycarbonate materials are inadequate in flame retardant performance in certain high-end technical fields, and the application of materials is restricted due to the potential policy restrictions used for flame retardants such as perfluorobutylsulfonate and polytetrafluoroethylene.

Method used

Develop a high impact fluorine-free, halogen-free flame retardant polycarbonate composition, by mixing it by using polycarbonate A and polycarbonate B with different melt indexes and prepared fluorine-free, halogen-free, polycarbonate flame retardant masterbatches Modified, octphenylcyclotetrasiloxane, silicon copolymer polycarbonate and methyl methacrylate-styrene-organosilicon core-shell copolymer were added to improve the flame retardancy, processing properties and mechanical properties of the material.

Benefits of technology

It realizes a polycarbonate composition with excellent flame retardant properties and good processing properties while ensuring high impact strength. Due to its fluorine-free and halogen-free properties, it will not be subject to policy restrictions and is suitable for the fields of home appliances and consumer electronics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505506A_ABST
    Figure CN119505506A_ABST
Patent Text Reader

Abstract

The invention discloses a high-impact-resistance fluoride-free halogen-free flame-retardant polycarbonate composition as well as a preparation method and application thereof. The polycarbonate composition comprises the following components: polycarbonate resin A, polycarbonate resin B, fluoride-free halogen-free polycarbonate flame-retardant master batches, a hindered phenol antioxidant, a phosphite ester antioxidant and pentaerythritol stearate. According to the invention, polycarbonate A and polycarbonate B with different melt indexes and the prepared fluoride-free halogen-free polycarbonate flame-retardant master batch are selected for blending modification, and octaphenylcyclotetrasiloxane in the fluoride-free halogen-free polycarbonate flame-retardant master batch can effectively improve the overall flame retardance and processability of the material and ensure good mechanical properties. The preparation method of the high-impact fluorine-free halogen-free flame-retardant polycarbonate composition provided by the invention is simple in formula components, simple in process, easy to control and excellent in comprehensive performance, and can be widely applied to the fields of household appliances, consumer electronics and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of materials, and in particular to a high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition, a preparation method and application thereof Background Art

[0002] Polycarbonate (PC) materials have become one of the five major general engineering plastics due to their excellent optical properties, outstanding toughness, high impact strength, excellent low-temperature impact resistance, good creep resistance and dimensional stability, high heat resistance, excellent transparency, high mechanical strength, low water absorption, non-toxicity and excellent dielectric properties. In recent years, the application of polycarbonate in various fields has shown a rapid growth trend, and its application range covers a wide range of important fields such as electronics and electrical, automotive materials, medical and health equipment, construction engineering, and emergency lighting. With the continuous advancement of science and technology, polycarbonate plastics have also shown a wide range of application prospects in many high-end technical fields, such as military industry, aerospace, electronic computers, optical fiber communications, etc., further reflecting its important value and potential as an advanced material.

[0003] Although polycarbonate (PC) has achieved a V-2 rating in the UL-94 test and its LOI (Limiting Oxygen Index) is about 25%, showing a certain degree of flame retardancy, however, this does not fully meet specific application areas, especially in the field of electronic materials that require higher flame retardancy. Therefore, it is particularly important to flame retardantly modify polycarbonate. In addition, during the combustion process of PC, in addition to its own combustion, dripping will also be produced, and these drippings may further ignite other combustible materials. In view of this, in order to effectively prevent the potential risks caused by melt dripping during the combustion process, in addition to flame retardants, anti-drip agents are usually added.

[0004] On February 7, 2023, the European Union released as scheduled the detailed information on the proposal jointly proposed by five countries on the restriction of perfluorinated or polyfluoroalkyl substances (PFAS). According to incomplete statistics, the proposal will restrict more than 10,000 types of PFAS substances, and its goal is to fundamentally and completely ban the production, use and sale of all more than 10,000 PFAS-containing chemicals. If this move is implemented, it will undoubtedly have a profound impact on the entire chemical industry and its supply chain. At present, potassium perfluorobutane sulfonate (PFBS) is a vital flame retardant in the field of polycarbonate (PC), but potassium perfluorobutane sulfonate (PFBS) is one of the restricted substances mentioned in the proposal. In addition to potassium perfluorobutane sulfonate (PFBS), polytetrafluoroethylene (PTFE), an anti-drip agent widely used in flame retardant polycarbonate, is also very likely to be restricted.

[0005] At present, there are few studies on fluorine-free and halogen-free flame-retardant polycarbonate in the domestic prior art. For example, Chinese patent CN117511167A discloses a low internal stress fluorine-free flame-retardant polycarbonate material, the composition of which includes 96-99 parts of polycarbonate resin, 0.3-0.7 parts of oxidized polyethylene wax, 0.2-0.4 parts of vinyl triethoxysilane, 0.1-0.3 parts of antioxidant, and 0.1-0.5 parts of lubricant. The preparation process of the low internal stress fluorine-free flame-retardant PC material of the invention is simple and easy, and the prepared alloy material can achieve a flame retardant effect of 1.5mmVO, and has lower internal stress than ordinary PC. It is suitable for automobiles, electronic appliances, wall switches, lighting and other fields, especially for electronic appliance housings that need to be screwed or glued. However, the invention does not provide thermodynamic properties such as impact strength and melt index. The high impact fluorine-free and halogen-free flame-retardant polycarbonate composition of the present invention ensures excellent flame retardant properties while ensuring high impact strength, and will not be restricted by policies because of fluorine-free and halogen-free. Summary of the invention

[0006] Based on this, the purpose of the present invention is to provide a high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition and a preparation method thereof. The polycarbonate composition prepared by the present invention has high impact performance, excellent flame retardancy and processing performance, and can be applied to the fields of home appliances and consumer electronics.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition, which is prepared from the following raw materials in parts by weight:

[0009]

[0010] The total weight fractions of polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free flame retardant masterbatch is 100 parts; the melt index of polycarbonate A is 8-12 g / 10 min at 300°C / 1.2 kg; the melt index of polycarbonate B is 2-4 g / 10 min at 300°C / 1.2 kg.

[0011] The method for preparing the fluorine-free and halogen-free polycarbonate flame retardant masterbatch comprises the following steps:

[0012] (1) In a three-necked flask equipped with a stirring device, a condenser and a thermometer, accurately weigh 150g of diphenyldimethoxysilane, 240g of acetone and 8g of deionized water, and then start the agitator until all the ingredients are fully mixed and evenly distributed. Next, dissolve 0.04g of NaOH in 16g of methanol, and after ensuring complete dissolution, slowly add this solution to the three-necked flask. Subsequently, raise the system temperature to 55 degrees Celsius, start the reflux device, and maintain this condition for 4 hours. After the reaction is completed, separate the product by suction filtration, wash it three times with anhydrous ethanol, and then wash it three times with deionized water until the filtrate is neutral. Finally, place the washed product in a vacuum dryer and dry it thoroughly to obtain white crystalline octaphenylcyclotetrasiloxane.

[0013] (2) The octaphenylcyclotetrasiloxane prepared in step (1) was placed in a vacuum oven at 80° C. and dried for 4 h.

[0014] (3) Place the silicon copolymer polycarbonate and polycarbonate resin A in a vacuum oven at 100° C. and dry for 4-6 hours.

[0015] (4) placing the octaphenylcyclotetrasiloxane dried in step (2) and step (3) and silicon copolymer polycarbonate, polycarbonate resin A, and methyl methacrylate-styrene-silicon core-shell copolymer in a mixing pot in a ratio of 10-20:15-35:40-60:3-8, wherein the total mass fraction of octaphenylcyclotetrasiloxane, silicon copolymer polycarbonate, polycarbonate resin A, and methyl methacrylate-styrene-silicon core-shell copolymer is 100 parts, and adding 0.05-0.3 parts of hindered phenol antioxidant, 0.05-0.3 parts of phosphite antioxidant, and 0.1-0.5 parts of pentaerythritol stearate for blending.

[0016] (5) The mixed material prepared in step (4) is fed into a twin-screw extruder through a feeding hopper at a uniform speed, and melt-extruded and granulated in the twin-screw extruder to obtain a fluorine-free and halogen-free polycarbonate flame retardant masterbatch.

[0017] The melting index of the silicon copolymer polycarbonate is 2-4g / 10min at 300℃ / 1.2kg, which is a low melting index silicon copolymer polycarbonate; the melting index of the polycarbonate resin A is 8-12g / 10min at 300℃ / 1.2kg, the hindered phenol antioxidant is preferably German BASF antioxidant Irganox 1076, Jinhai Yabao AT-76, the phosphite antioxidant is preferably German BASF Irganox 168, Jinhai Yabao AT-168, the pentaerythritol stearate is preferably Italian PETS-HS, German PETS-HS. The methyl methacrylate-styrene-silicon core-shell copolymer is preferably Japanese Mitsubishi S-2001 and Paster S203.

[0018] In some embodiments, the hindered phenol antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl ester, and the phosphite antioxidant is bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphate.

[0019] Another object of the present invention is to provide a method for preparing the above-mentioned high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition.

[0020] The specific technical solutions are as follows:

[0021] (1) The polycarbonate resin A, the polycarbonate resin B, and the fluorine-free and halogen-free polycarbonate flame retardant masterbatch are placed in a vacuum oven at 100-110° C. and dried for 4-6 hours.

[0022] (2) mixing the polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free polycarbonate flame retardant masterbatch obtained by drying in step (1);

[0023] (3) mixing the hindered phenol antioxidant, the phosphite antioxidant, and pentaerythritol stearate;

[0024] (4) mixing the mixed material obtained in step (2) and the mixed material obtained in step (3);

[0025] (5) The mixed material obtained in step (4) is fed into a twin-screw extruder through a feeding hopper at a uniform speed, and melt-extruded and granulated in the twin-screw extruder to obtain a high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition.

[0026] In some embodiments, melt extrusion is carried out in a twin-screw extruder, and the process parameters for granulation include: zone 1 temperature of 220-240°C, zone 2 temperature of 225-255°C, zone 3 temperature of 230-260°C, zone 4 temperature of 225-260°C, zone 5 temperature of 225-260°C, zone 6 temperature of 225-260°C, zone 7 temperature of 225-260°C, zone 8 temperature of 225-260°C, die head temperature of 250-270°C, and screw speed of 300-600rpm;

[0027] In some embodiments, in the mixing of step (2), the rotation speed of the mixing pot is 400-600 r / min and the mixing time is 5-10 min.

[0028] In some embodiments, in the mixing of step (3), the rotation speed of the mixing pot is 300-600 r / min, and the mixing time is 5-10 min.

[0029] In some embodiments, in the mixing of step (4), the rotation speed of the mixing pot is 400-600 r / min, and the mixing time is 8-12 min.

[0030] In some embodiments, the screw shape of the parallel twin-screw extruder is a single-line screw.

[0031] In some of the embodiments, the ratio L / D of the screw length L and the diameter D of the parallel twin-screw extruder is 35 to 50; the screw is provided with more than one (including one) meshing block area and more than one (including one) reverse thread area.

[0032] In some embodiments, the ratio L / D of the screw length L to the screw diameter D is 35-45; and the screw is provided with two meshing block areas and one reverse thread area.

[0033] The principles of the high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition and the preparation method thereof of the present invention are as follows:

[0034] Different from the traditional modification of polycarbonate compositions, the present invention selects polycarbonate A and polycarbonate B with different melt indexes and the prepared fluorine-free and halogen-free polycarbonate flame retardant masterbatch for blending modification. The octaphenylcyclotetrasiloxane in the fluorine-free and halogen-free polycarbonate flame retardant masterbatch can effectively improve the overall flame retardancy and processing performance of the material, and ensure good mechanical properties. In the fluorine-free and halogen-free polycarbonate flame retardant masterbatch, the methyl methacrylate-styrene-organic silicon core-shell copolymer used, compared with the traditional methyl methacrylate-styrene-butadiene copolymer, achieves a significant improvement in the chemical resistance and impact resistance of the material by replacing butadiene with silicone. This improvement enables the polycarbonate composition to exhibit higher toughness and chemical resistance, thereby ensuring the long-term application of the material in harsh environments, and its performance retention rate will not decrease, so that the fluorine-free and halogen-free polycarbonate flame retardant masterbatch does not need to add a toughening agent after being added to the system.

[0035] The antioxidant used in the present invention is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl ester, which exhibits excellent thermal stability during the blending process of the polycarbonate composition, and the hindered piperidine group contained therein can provide an antioxidant effect while enhancing the dyeing performance of the copolymer. The melting point of bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphate is as high as 239°C, and the thermal decomposition temperature exceeds 350°C, and it has excellent heat resistance and hydrolysis resistance. The substance can provide excellent color stability and melt stability for the modified polycarbonate material during high-speed blending, while effectively preventing the thermal degradation of polycarbonate, flame retardants and other small molecule additives during high-temperature processing, and can inhibit the long-term thermal oxygen discoloration phenomenon. In addition, the antioxidant also gives the material color stability in a nitrogen oxide (NOx) gas environment, avoiding the problem of gas fumigation discoloration.

[0036] The pentaerythritol stearate used in the present invention has the dual effects of enhancing the demoulding performance of the material and improving the thermal stability. When used independently as a lubricant, it can significantly reduce the shear force of the screw on the material and reduce the performance damage suffered by the material during the physical shearing process.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] The present invention selects polycarbonate A and polycarbonate B with different melt indexes and prepared fluorine-free and halogen-free polycarbonate flame retardant masterbatch for blending and modification. The octaphenylcyclotetrasiloxane in the fluorine-free and halogen-free polycarbonate flame retardant masterbatch can effectively improve the flame retardancy and processing performance of the material as a whole, and ensure good mechanical properties. In addition, in order to avoid using fluorine-containing components without reducing flame retardancy and mechanical properties, the present invention uses octaphenylcyclotetrasiloxane and low melt index silicon copolymer polycarbonate to prepare fluorine-free and halogen-free polycarbonate flame retardant masterbatch to ensure that the material is fluorine-free and halogen-free. The low melt index silicon copolymer polycarbonate has a low melt index, weak fluidity, and strong melt strength. In addition, a high silicon content can effectively improve the impact resistance of the material and the carbonization efficiency during combustion, improve the melt strength and flame retardancy of the material as a whole, so that the material can be quickly carbonized and extinguished during combustion, and there is no dripping tendency, thereby avoiding the use of a commonly used anti-dripping agent through polytetrafluoroethylene (PTFE). After the fluorine-free and halogen-free polycarbonate flame retardant masterbatch is added to the material for melt blending, octaphenylcyclotetrasiloxane is evenly distributed in the polycarbonate. After combustion, the carbon layer will become denser with the addition of octaphenylcyclotetrasiloxane. Moreover, when octaphenylcyclotetrasiloxane is added, the residual carbon rate after thermal weight loss test in air atmosphere is significantly improved.

[0039] The preparation method of the high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition provided by the present invention has simple formula components, simple process, easy control, excellent comprehensive performance, and can be widely used in the fields of home appliances and consumer electronics. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 The present invention is a flow chart of the preparation process of a high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition according to an embodiment of the present invention. DETAILED DESCRIPTION

[0041] Unless otherwise specified, the components involved in the embodiments and comparative examples of the present invention are as follows:

[0042] The raw materials used in the examples and comparative examples of the present invention are as follows:

[0043] Polycarbonate resin A, with a melt index of 10 g / 10 min at 300°C / 1.2 kg, selected from Wanhua Chemical Group Co., Ltd.;

[0044] Polycarbonate resin B, with a melt index of 3 g / 10 min at 300°C / 1.2 kg, was selected from LG Chemical Co., Ltd. of South Korea;

[0045] The hindered phenol antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl ester, selected from BASF GmbH, Germany;

[0046] The phosphite antioxidant is bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate, selected from BASF GmbH of Germany;

[0047] Pentaerythritol stearate, selected from Zhaoqing Sendeli Chemical Industry Co., Ltd.

[0048] Silicone copolymer polycarbonate, selected from LG Chemical Co., Ltd.

[0049] The methyl methacrylate-styrene-silicon core-shell copolymer is S-2001 from Mitsubishi, Japan.

[0050] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the embodiments, and preferred embodiments of the present invention are given below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. The purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0051] Embodiment 1:

[0052] The present embodiment provides a high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition, which is prepared from the following raw materials in parts by weight:

[0053]

[0054] The total weight of polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free flame retardant masterbatch is 100 parts.

[0055] The above-mentioned high impact fluorine-free and halogen-free flame retardant polycarbonate composition method, reference Figure 1 , including the following steps:

[0056] (1) The polycarbonate resin A, the polycarbonate resin B, and the fluorine-free and halogen-free polycarbonate flame retardant masterbatch were placed in a vacuum oven at 100° C. and dried for 4 hours.

[0057] (2) The polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free polycarbonate flame retardant masterbatch dried in step (1) are mixed, the speed of the mixing pot is 500 r / min, and the mixing time is 8 min.

[0058] (3) The hindered phenol antioxidant, the phosphite antioxidant and pentaerythritol stearate are mixed, the rotation speed of the mixing pot is 300 r / min, and the mixing time is 5 min.

[0059] (4) mixing the mixed material obtained in step (2) and the mixed material obtained in step (3); the rotating speed of the mixing pot is 500 r / min, and the mixing time is 10 min.

[0060] (5) adding the mixed material obtained in step (4) into a twin-screw extruder through a feeding hopper at a uniform speed, and performing melt extrusion and granulation in the twin-screw extruder. The process parameters of granulation include: a temperature of zone 1 of 230° C., a temperature of zone 2 of 235° C., a temperature of zone 3 of 240° C., a temperature of zone 4 of 245° C., a temperature of zone 5 of 250° C., a temperature of zone 6 of 250° C., a temperature of zone 7 of 250° C., a temperature of zone 8 of 245° C., a die head temperature of 265° C., and a screw speed of 500 rpm. The twin-screw extruder has a single-thread screw shape, a ratio of screw length L to diameter D of L / D of 35, and two meshing block areas and one reverse thread area are provided on the screw.

[0061] The preparation method of the fluorine-free and halogen-free polycarbonate flame retardant masterbatch used in Example 1 is as follows:

[0062] (1) In a three-necked flask equipped with a stirring device, a condenser and a thermometer, accurately weigh 150g of diphenyldimethoxysilane, 240g of acetone and 8g of deionized water, and then start the agitator until all the ingredients are fully mixed and evenly distributed. Next, dissolve 0.04g of NaOH in 16g of methanol, and after ensuring complete dissolution, slowly add this solution to the three-necked flask. Subsequently, raise the system temperature to 55 degrees Celsius, start the reflux device, and maintain this condition for 4 hours. After the reaction is completed, separate the product by suction filtration, wash it three times with anhydrous ethanol, and then wash it three times with deionized water until the filtrate is neutral. Finally, place the washed product in a vacuum dryer and dry it thoroughly to obtain white crystalline octaphenylcyclotetrasiloxane.

[0063] (2) The octaphenylcyclotetrasiloxane prepared in step (1) was placed in a vacuum oven at 80° C. and dried for 4 h.

[0064] (3) Place the silicon copolymer polycarbonate and polycarbonate resin A in a vacuum oven at 100° C. and dry for 4-6 hours.

[0065] (4) The octaphenylcyclotetrasiloxane dried in step (2) and step (3) is placed in a mixing pot with silicon copolymer polycarbonate, polycarbonate resin A, and methyl methacrylate-styrene-silicon core-shell copolymer in a ratio of 20:35:40:5, wherein the total mass fraction of octaphenylcyclotetrasiloxane, silicon copolymer polycarbonate, polycarbonate resin A, and methyl methacrylate-styrene-silicon core-shell copolymer is 100 parts, and 0.1 part of hindered phenol antioxidant, 0.2 part of phosphite antioxidant, and 0.3 part of pentaerythritol stearate are added for blending.

[0066] (5) The mixed material prepared in step (4) is fed into a twin-screw extruder through a feeding hopper at a uniform speed, and melt-extruded and granulated in the twin-screw extruder to obtain a fluorine-free and halogen-free polycarbonate flame retardant masterbatch.

[0067] Embodiment 2:

[0068] The present embodiment provides a high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition, which is prepared from the following raw materials in parts by weight:

[0069]

[0070]

[0071] The total weight of polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free flame retardant masterbatch is 100 parts.

[0072] The above-mentioned high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition method comprises the following steps:

[0073] (1) The polycarbonate resin A, the polycarbonate resin B, and the fluorine-free and halogen-free polycarbonate flame retardant masterbatch were placed in a vacuum oven at 100° C. and dried for 4 hours.

[0074] (2) The polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free polycarbonate flame retardant masterbatch dried in step (1) are mixed, the speed of the mixing pot is 500 r / min, and the mixing time is 8 min.

[0075] (3) The hindered phenol antioxidant, the phosphite antioxidant and pentaerythritol stearate are mixed, the rotation speed of the mixing pot is 500 r / min, and the mixing time is 8 min.

[0076] (4) mixing the mixed material obtained in step (2) and the mixed material obtained in step (3); the rotating speed of the mixing pot is 500 r / min, and the mixing time is 10 min.

[0077] (5) adding the mixed material obtained in step (4) into a twin-screw extruder through a feeding hopper at a uniform speed, and performing melt extrusion and granulation in the twin-screw extruder. The process parameters of granulation include: a temperature of zone 1 of 230° C., a temperature of zone 2 of 235° C., a temperature of zone 3 of 240° C., a temperature of zone 4 of 245° C., a temperature of zone 5 of 250° C., a temperature of zone 6 of 250° C., a temperature of zone 7 of 250° C., a temperature of zone 8 of 245° C., a die head temperature of 265° C., and a screw speed of 500 rpm. The twin-screw extruder has a single-thread screw shape, a ratio of screw length L to diameter D of L / D of 35, and two meshing block areas and one reverse thread area are provided on the screw.

[0078] The preparation method of the fluorine-free and halogen-free polycarbonate flame retardant masterbatch used in Example 2 is as follows:

[0079] (1) In a three-necked flask equipped with a stirring device, a condenser and a thermometer, accurately weigh 150g of diphenyldimethoxysilane, 240g of acetone and 8g of deionized water, and then start the agitator until all the ingredients are fully mixed and evenly distributed. Next, dissolve 0.04g of NaOH in 16g of methanol, and after ensuring complete dissolution, slowly add this solution to the three-necked flask. Subsequently, raise the system temperature to 55 degrees Celsius, start the reflux device, and maintain this condition for 4 hours. After the reaction is completed, separate the product by suction filtration, wash it three times with anhydrous ethanol, and then wash it three times with deionized water until the filtrate is neutral. Finally, place the washed product in a vacuum dryer and dry it thoroughly to obtain white crystalline octaphenylcyclotetrasiloxane.

[0080] (2) The octaphenylcyclotetrasiloxane prepared in step (1) was placed in a vacuum oven at 80° C. and dried for 4 h.

[0081] (3) Place the silicon copolymer polycarbonate and polycarbonate resin A in a vacuum oven at 100° C. and dry for 4-6 hours.

[0082] (4) The octaphenylcyclotetrasiloxane dried in step (2) and step (3) is placed in a mixing pot with silicon copolymer polycarbonate, polycarbonate resin A, and methyl methacrylate-styrene-silicon core-shell copolymer in a ratio of 20:35:40:5, wherein the total mass fraction of octaphenylcyclotetrasiloxane, silicon copolymer polycarbonate, polycarbonate resin A, and methyl methacrylate-styrene-silicon core-shell copolymer is 100 parts, and 0.1 part of hindered phenol antioxidant, 0.2 part of phosphite antioxidant, and 0.3 part of pentaerythritol stearate are added for blending.

[0083] (5) The mixed material prepared in step (4) is fed into a twin-screw extruder through a feeding hopper at a uniform speed, and melt-extruded and granulated in the twin-screw extruder to obtain a fluorine-free and halogen-free polycarbonate flame retardant masterbatch.

[0084] Embodiment 3:

[0085] The present embodiment provides a high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition, which is prepared from the following raw materials in parts by weight:

[0086]

[0087] The total weight of polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free flame retardant masterbatch is 100 parts.

[0088] The above-mentioned high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition method comprises the following steps:

[0089] (1) The polycarbonate resin A, the polycarbonate resin B, and the fluorine-free and halogen-free polycarbonate flame retardant masterbatch were placed in a vacuum oven at 100° C. and dried for 4 hours.

[0090] (2) The polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free polycarbonate flame retardant masterbatch dried in step (1) are mixed, the speed of the mixing pot is 500 r / min, and the mixing time is 8 min.

[0091] (3) The hindered phenol antioxidant, the phosphite antioxidant and pentaerythritol stearate are mixed, the rotation speed of the mixing pot is 500 r / min, and the mixing time is 8 min.

[0092] (4) mixing the mixed material obtained in step (2) and the mixed material obtained in step (3); the rotating speed of the mixing pot is 500 r / min, and the mixing time is 10 min.

[0093] (5) adding the mixed material obtained in step (4) into a twin-screw extruder through a feeding hopper at a uniform speed, and performing melt extrusion and granulation in the twin-screw extruder. The process parameters of granulation include: a temperature of zone 1 of 230° C., a temperature of zone 2 of 235° C., a temperature of zone 3 of 240° C., a temperature of zone 4 of 245° C., a temperature of zone 5 of 250° C., a temperature of zone 6 of 250° C., a temperature of zone 7 of 250° C., a temperature of zone 8 of 245° C., a die head temperature of 265° C., and a screw speed of 500 rpm. The twin-screw extruder has a single-thread screw shape, a ratio of screw length L to diameter D of L / D of 35, and two meshing block areas and one reverse thread area are provided on the screw.

[0094] The preparation method of the fluorine-free and halogen-free polycarbonate flame retardant masterbatch used in Example 3 is as follows:

[0095] (1) In a three-necked flask equipped with a stirring device, a condenser and a thermometer, accurately weigh 150g of diphenyldimethoxysilane, 240g of acetone and 8g of deionized water, and then start the agitator until all the ingredients are fully mixed and evenly distributed. Next, dissolve 0.04g of NaOH in 16g of methanol, and after ensuring complete dissolution, slowly add this solution to the three-necked flask. Subsequently, raise the system temperature to 55 degrees Celsius, start the reflux device, and maintain this condition for 4 hours. After the reaction is completed, separate the product by suction filtration, wash it three times with anhydrous ethanol, and then wash it three times with deionized water until the filtrate is neutral. Finally, place the washed product in a vacuum dryer and dry it thoroughly to obtain white crystalline octaphenylcyclotetrasiloxane.

[0096] (2) The octaphenylcyclotetrasiloxane prepared in step (1) was placed in a vacuum oven at 80° C. and dried for 4 h.

[0097] (3) Place the silicon copolymer polycarbonate and polycarbonate resin A in a vacuum oven at 100° C. and dry for 4-6 hours.

[0098] (4) The octaphenylcyclotetrasiloxane dried in step (2) and step (3) is placed in a mixing pot with silicon copolymer polycarbonate, polycarbonate resin A, and methyl methacrylate-styrene-silicon core-shell copolymer in a ratio of 20:35:40:5, wherein the total mass fraction of octaphenylcyclotetrasiloxane, silicon copolymer polycarbonate, polycarbonate resin A, and methyl methacrylate-styrene-silicon core-shell copolymer is 100 parts, and 0.1 part of hindered phenol antioxidant, 0.2 part of phosphite antioxidant, and 0.3 part of pentaerythritol stearate are added for blending.

[0099] (5) The mixed material prepared in step (4) is fed into a twin-screw extruder through a feeding hopper at a uniform speed, and melt-extruded and granulated in the twin-screw extruder to obtain a fluorine-free and halogen-free polycarbonate flame retardant masterbatch.

[0100] Embodiment 4:

[0101] The present embodiment provides a high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition, which is prepared from the following raw materials in parts by weight:

[0102]

[0103] The total weight of polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free flame retardant masterbatch is 100 parts.

[0104] The above-mentioned high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition method comprises the following steps:

[0105] (1) The polycarbonate resin A, the polycarbonate resin B, and the fluorine-free and halogen-free polycarbonate flame retardant masterbatch were placed in a vacuum oven at 100° C. and dried for 4 hours.

[0106] (2) The polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free polycarbonate flame retardant masterbatch dried in step (1) are mixed, the speed of the mixing pot is 500 r / min, and the mixing time is 8 min.

[0107] (3) The hindered phenol antioxidant, the phosphite antioxidant and pentaerythritol stearate are mixed, the rotation speed of the mixing pot is 500 r / min, and the mixing time is 8 min.

[0108] (4) mixing the mixed material obtained in step (2) and the mixed material obtained in step (3); the rotating speed of the mixing pot is 500 r / min, and the mixing time is 10 min.

[0109] (5) adding the mixed material obtained in step (4) into a twin-screw extruder through a feeding hopper at a uniform speed, and performing melt extrusion and granulation in the twin-screw extruder. The process parameters of granulation include: a temperature of zone 1 of 230° C., a temperature of zone 2 of 235° C., a temperature of zone 3 of 240° C., a temperature of zone 4 of 245° C., a temperature of zone 5 of 250° C., a temperature of zone 6 of 250° C., a temperature of zone 7 of 250° C., a temperature of zone 8 of 245° C., a die head temperature of 265° C., and a screw speed of 500 rpm. The twin-screw extruder has a single-thread screw shape, a ratio of screw length L to diameter D of L / D of 35, and two meshing block areas and one reverse thread area are provided on the screw.

[0110] The preparation method of the fluorine-free and halogen-free polycarbonate flame retardant masterbatch used in Example 4 is as follows:

[0111] (1) In a three-necked flask equipped with a stirring device, a condenser and a thermometer, accurately weigh 150g of diphenyldimethoxysilane, 240g of acetone and 8g of deionized water, and then start the agitator until all the ingredients are fully mixed and evenly distributed. Next, dissolve 0.04g of NaOH in 16g of methanol, and after ensuring complete dissolution, slowly add this solution to the three-necked flask. Subsequently, raise the system temperature to 55 degrees Celsius, start the reflux device, and maintain this condition for 4 hours. After the reaction is completed, separate the product by suction filtration, wash it three times with anhydrous ethanol, and then wash it three times with deionized water until the filtrate is neutral. Finally, place the washed product in a vacuum dryer and dry it thoroughly to obtain white crystalline octaphenylcyclotetrasiloxane.

[0112] (2) The octaphenylcyclotetrasiloxane prepared in step (1) was placed in a vacuum oven at 80° C. and dried for 4 h.

[0113] (3) Place the silicon copolymer polycarbonate and polycarbonate resin A in a vacuum oven at 100° C. and dry for 4-6 hours.

[0114] (4) The octaphenylcyclotetrasiloxane dried in step (2) and step (3) is placed in a mixing pot with silicon copolymer polycarbonate, polycarbonate resin A, and methyl methacrylate-styrene-silicon core-shell copolymer in a ratio of 20:35:40:5, wherein the total mass fraction of octaphenylcyclotetrasiloxane, silicon copolymer polycarbonate, polycarbonate resin A, and methyl methacrylate-styrene-silicon core-shell copolymer is 100 parts, and 0.1 part of hindered phenol antioxidant, 0.2 part of phosphite antioxidant, and 0.3 part of pentaerythritol stearate are added for blending.

[0115] (5) The mixed material prepared in step (4) is fed into a twin-screw extruder through a feeding hopper at a uniform speed, and melt-extruded and granulated in the twin-screw extruder to obtain a fluorine-free and halogen-free polycarbonate flame retardant masterbatch.

[0116] Embodiment 5:

[0117] The present embodiment provides a high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition, which is prepared from the following raw materials in parts by weight:

[0118]

[0119] The total weight of polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free flame retardant masterbatch is 100 parts.

[0120] The above-mentioned high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition method comprises the following steps:

[0121] (1) The polycarbonate resin A, the polycarbonate resin B, and the fluorine-free and halogen-free polycarbonate flame retardant masterbatch were placed in a vacuum oven at 100° C. and dried for 4 hours.

[0122] (2) The polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free polycarbonate flame retardant masterbatch dried in step (1) are mixed, the speed of the mixing pot is 500 r / min, and the mixing time is 8 min.

[0123] (3) The hindered phenol antioxidant, the phosphite antioxidant and pentaerythritol stearate are mixed, the rotation speed of the mixing pot is 500 r / min, and the mixing time is 8 min.

[0124] (4) mixing the mixed material obtained in step (2) and the mixed material obtained in step (3); the rotating speed of the mixing pot is 500 r / min, and the mixing time is 10 min.

[0125] (5) adding the mixed material obtained in step (4) into a twin-screw extruder through a feeding hopper at a uniform speed, and performing melt extrusion and granulation in the twin-screw extruder. The process parameters of granulation include: a temperature of zone 1 of 230° C., a temperature of zone 2 of 235° C., a temperature of zone 3 of 240° C., a temperature of zone 4 of 245° C., a temperature of zone 5 of 250° C., a temperature of zone 6 of 250° C., a temperature of zone 7 of 250° C., a temperature of zone 8 of 245° C., a die head temperature of 265° C., and a screw speed of 500 rpm. The twin-screw extruder has a single-thread screw shape, a ratio of screw length L to diameter D of L / D of 35, and two meshing block areas and one reverse thread area are provided on the screw.

[0126] The preparation method of the fluorine-free and halogen-free polycarbonate flame retardant masterbatch used in Example 5 is as follows:

[0127] (1) In a three-necked flask equipped with a stirring device, a condenser and a thermometer, accurately weigh 150g of diphenyldimethoxysilane, 240g of acetone and 8g of deionized water, and then start the agitator until all the ingredients are fully mixed and evenly distributed. Next, dissolve 0.04g of NaOH in 16g of methanol, and after ensuring complete dissolution, slowly add this solution to the three-necked flask. Subsequently, raise the system temperature to 55 degrees Celsius, start the reflux device, and maintain this condition for 4 hours. After the reaction is completed, separate the product by suction filtration, wash it three times with anhydrous ethanol, and then wash it three times with deionized water until the filtrate is neutral. Finally, place the washed product in a vacuum dryer and dry it thoroughly to obtain white crystalline octaphenylcyclotetrasiloxane.

[0128] (2) The octaphenylcyclotetrasiloxane prepared in step (1) was placed in a vacuum oven at 80° C. and dried for 4 h.

[0129] (3) Place the silicon copolymer polycarbonate and polycarbonate resin A in a vacuum oven at 100° C. and dry for 4-6 hours.

[0130] (4) The octaphenylcyclotetrasiloxane dried in step (2) and step (3) is placed in a mixing pot with silicon copolymer polycarbonate, polycarbonate resin A, and methyl methacrylate-styrene-silicon core-shell copolymer in a ratio of 20:35:48:7, wherein the total mass fraction of octaphenylcyclotetrasiloxane, silicon copolymer polycarbonate, polycarbonate resin A, and methyl methacrylate-styrene-silicon core-shell copolymer is 100 parts, and 0.1 part of hindered phenol antioxidant, 0.2 part of phosphite antioxidant, and 0.3 part of pentaerythritol stearate are added for blending.

[0131] (5) The mixed material prepared in step (4) is fed into a twin-screw extruder through a feeding hopper at a uniform speed, and melt-extruded and granulated in the twin-screw extruder to obtain a fluorine-free and halogen-free polycarbonate flame retardant masterbatch.

[0132] Embodiment 6:

[0133] The present embodiment provides a high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition, which is prepared from the following raw materials in parts by weight:

[0134]

[0135] The total weight of polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free flame retardant masterbatch is 100 parts.

[0136] The above-mentioned high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition method comprises the following steps:

[0137] (3) The polycarbonate resin A, polycarbonate resin B, and fluorine-free and halogen-free polycarbonate flame retardant masterbatch were placed in a vacuum oven at 100° C. and dried for 4 hours.

[0138] (4) The polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free polycarbonate flame retardant masterbatch dried in step (1) are mixed, the speed of the mixing pot is 500 r / min, and the mixing time is 8 min.

[0139] (3) The hindered phenol antioxidant, the phosphite antioxidant and pentaerythritol stearate are mixed, the rotation speed of the mixing pot is 500 r / min, and the mixing time is 8 min.

[0140] (4) mixing the mixed material obtained in step (2) and the mixed material obtained in step (3); the rotating speed of the mixing pot is 500 r / min, and the mixing time is 10 min.

[0141] (5) adding the mixed material obtained in step (4) into a twin-screw extruder through a feeding hopper at a uniform speed, and performing melt extrusion and granulation in the twin-screw extruder. The process parameters of granulation include: a temperature of zone 1 of 230° C., a temperature of zone 2 of 235° C., a temperature of zone 3 of 240° C., a temperature of zone 4 of 245° C., a temperature of zone 5 of 250° C., a temperature of zone 6 of 250° C., a temperature of zone 7 of 250° C., a temperature of zone 8 of 245° C., a die head temperature of 265° C., and a screw speed of 500 rpm. The twin-screw extruder has a single-thread screw shape, a ratio of screw length L to diameter D of L / D of 35, and two meshing block areas and one reverse thread area are provided on the screw.

[0142] The preparation method of the fluorine-free and halogen-free polycarbonate flame retardant masterbatch used in Example 6 is as follows:

[0143] (1) In a three-necked flask equipped with a stirring device, a condenser and a thermometer, accurately weigh 150g of diphenyldimethoxysilane, 240g of acetone and 8g of deionized water, and then start the agitator until all the ingredients are fully mixed and evenly distributed. Next, dissolve 0.04g of NaOH in 16g of methanol, and after ensuring complete dissolution, slowly add this solution to the three-necked flask. Subsequently, raise the system temperature to 55 degrees Celsius, start the reflux device, and maintain this condition for 4 hours. After the reaction is completed, separate the product by suction filtration, wash it three times with anhydrous ethanol, and then wash it three times with deionized water until the filtrate is neutral. Finally, place the washed product in a vacuum dryer and dry it thoroughly to obtain white crystalline octaphenylcyclotetrasiloxane.

[0144] (2) The octaphenylcyclotetrasiloxane prepared in step (1) was placed in a vacuum oven at 80° C. and dried for 4 h.

[0145] (3) Place the silicon copolymer polycarbonate and polycarbonate resin A in a vacuum oven at 100° C. and dry for 4-6 hours.

[0146] (4) The octaphenylcyclotetrasiloxane dried in step (2) and step (3) is placed in a mixing pot with silicon copolymer polycarbonate, polycarbonate resin A, and methyl methacrylate-styrene-silicon core-shell copolymer in a ratio of 20:35:40:5, wherein the total mass fraction of octaphenylcyclotetrasiloxane, silicon copolymer polycarbonate, polycarbonate resin A, and methyl methacrylate-styrene-silicon core-shell copolymer is 100 parts, and 0.1 part of hindered phenol antioxidant, 0.2 part of phosphite antioxidant, and 0.3 part of pentaerythritol stearate are added for blending.

[0147] (5) The mixed material prepared in step (4) is fed into a twin-screw extruder through a feeding hopper at a uniform speed, and melt-extruded and granulated in the twin-screw extruder to obtain a fluorine-free and halogen-free polycarbonate flame retardant masterbatch.

[0148] Embodiment 7:

[0149] The present embodiment provides a high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition, which is prepared from the following raw materials in parts by weight:

[0150]

[0151]

[0152] The total weight of polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free flame retardant masterbatch is 100 parts.

[0153] The above-mentioned high impact fluorine-free and halogen-free flame retardant polycarbonate composition method, reference Figure 1 , including the following steps:

[0154] (2) The polycarbonate resin A, the polycarbonate resin B, and the fluorine-free and halogen-free polycarbonate flame retardant masterbatch were placed in a vacuum oven at 100° C. and dried for 4 hours.

[0155] (2) The polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free polycarbonate flame retardant masterbatch dried in step (1) are mixed, the speed of the mixing pot is 500 r / min, and the mixing time is 8 min.

[0156] (3) The hindered phenol antioxidant, the phosphite antioxidant and pentaerythritol stearate are mixed, the rotation speed of the mixing pot is 300 r / min, and the mixing time is 5 min.

[0157] (4) mixing the mixed material obtained in step (2) and the mixed material obtained in step (3); the rotating speed of the mixing pot is 500 r / min, and the mixing time is 10 min.

[0158] (5) adding the mixed material obtained in step (4) into a twin-screw extruder through a feeding hopper at a uniform speed, and performing melt extrusion and granulation in the twin-screw extruder. The process parameters of granulation include: a temperature of zone 1 of 230° C., a temperature of zone 2 of 235° C., a temperature of zone 3 of 240° C., a temperature of zone 4 of 245° C., a temperature of zone 5 of 250° C., a temperature of zone 6 of 250° C., a temperature of zone 7 of 250° C., a temperature of zone 8 of 245° C., a die head temperature of 265° C., and a screw speed of 500 rpm. The twin-screw extruder has a single-thread screw shape, a ratio of screw length L to diameter D of L / D of 35, and two meshing block areas and one reverse thread area are provided on the screw.

[0159] The preparation method of the fluorine-free and halogen-free polycarbonate flame retardant masterbatch used in Example 1 is as follows:

[0160] (1) In a three-necked flask equipped with a stirring device, a condenser and a thermometer, accurately weigh 150g of diphenyldimethoxysilane, 240g of acetone and 8g of deionized water, and then start the agitator until all the ingredients are fully mixed and evenly distributed. Next, dissolve 0.04g of NaOH in 16g of methanol, and after ensuring complete dissolution, slowly add this solution to the three-necked flask. Subsequently, raise the system temperature to 55 degrees Celsius, start the reflux device, and maintain this condition for 4 hours. After the reaction is completed, separate the product by suction filtration, wash it three times with anhydrous ethanol, and then wash it three times with deionized water until the filtrate is neutral. Finally, place the washed product in a vacuum dryer and dry it thoroughly to obtain white crystalline octaphenylcyclotetrasiloxane.

[0161] (2) The octaphenylcyclotetrasiloxane prepared in step (1) was placed in a vacuum oven at 80° C. and dried for 4 h.

[0162] (3) Place the silicon copolymer polycarbonate and polycarbonate resin A in a vacuum oven at 100° C. and dry for 4-6 hours.

[0163] (4) The octaphenylcyclotetrasiloxane dried in step (2) and step (3) is placed in a mixing pot with silicon copolymer polycarbonate, polycarbonate resin A, and methyl methacrylate-styrene-silicon core-shell copolymer in a ratio of 20:15:60:5, wherein the total mass fraction of octaphenylcyclotetrasiloxane, silicon copolymer polycarbonate, polycarbonate resin A, and methyl methacrylate-styrene-silicon core-shell copolymer is 100 parts, and 0.1 part of hindered phenol antioxidant, 0.2 part of phosphite antioxidant, and 0.3 part of pentaerythritol stearate are added for blending.

[0164] (5) The mixed material prepared in step (4) is fed into a twin-screw extruder through a feeding hopper at a uniform speed, and melt-extruded and granulated in the twin-screw extruder to obtain a fluorine-free and halogen-free polycarbonate flame retardant masterbatch.

[0165] Embodiment 8:

[0166] The present embodiment provides a high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition, which is prepared from the following raw materials in parts by weight:

[0167]

[0168] The total weight of polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free flame retardant masterbatch is 100 parts.

[0169] The above-mentioned high impact fluorine-free and halogen-free flame retardant polycarbonate composition method, reference Figure 1 , including the following steps:

[0170] (3) The polycarbonate resin A, polycarbonate resin B, and fluorine-free and halogen-free polycarbonate flame retardant masterbatch were placed in a vacuum oven at 100° C. and dried for 4 hours.

[0171] (2) The polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free polycarbonate flame retardant masterbatch dried in step (1) are mixed, the speed of the mixing pot is 500 r / min, and the mixing time is 8 min.

[0172] (3) The hindered phenol antioxidant, the phosphite antioxidant and pentaerythritol stearate are mixed, the rotation speed of the mixing pot is 300 r / min, and the mixing time is 5 min.

[0173] (4) mixing the mixed material obtained in step (2) and the mixed material obtained in step (3); the rotating speed of the mixing pot is 500 r / min, and the mixing time is 10 min.

[0174] (5) adding the mixed material obtained in step (4) into a twin-screw extruder through a feeding hopper at a uniform speed, and performing melt extrusion and granulation in the twin-screw extruder. The process parameters of granulation include: a temperature of zone 1 of 230° C., a temperature of zone 2 of 235° C., a temperature of zone 3 of 240° C., a temperature of zone 4 of 245° C., a temperature of zone 5 of 250° C., a temperature of zone 6 of 250° C., a temperature of zone 7 of 250° C., a temperature of zone 8 of 245° C., a die head temperature of 265° C., and a screw speed of 500 rpm. The twin-screw extruder has a single-thread screw shape, a ratio of screw length L to diameter D of L / D of 35, and two meshing block areas and one reverse thread area are provided on the screw.

[0175] The preparation method of the fluorine-free and halogen-free polycarbonate flame retardant masterbatch used in Example 1 is as follows:

[0176] (1) In a three-necked flask equipped with a stirring device, a condenser and a thermometer, accurately weigh 150g of diphenyldimethoxysilane, 240g of acetone and 8g of deionized water, and then start the agitator until all the ingredients are fully mixed and evenly distributed. Next, dissolve 0.04g of NaOH in 16g of methanol, and after ensuring complete dissolution, slowly add this solution to the three-necked flask. Subsequently, raise the system temperature to 55 degrees Celsius, start the reflux device, and maintain this condition for 4 hours. After the reaction is completed, separate the product by suction filtration, wash it three times with anhydrous ethanol, and then wash it three times with deionized water until the filtrate is neutral. Finally, place the washed product in a vacuum dryer and dry it thoroughly to obtain white crystalline octaphenylcyclotetrasiloxane.

[0177] (2) The octaphenylcyclotetrasiloxane prepared in step (1) was placed in a vacuum oven at 80° C. and dried for 4 h.

[0178] (3) Place the silicon copolymer polycarbonate and polycarbonate resin A in a vacuum oven at 100° C. and dry for 4-6 hours.

[0179] (4) The octaphenylcyclotetrasiloxane dried in step (2) and step (3) and silicon copolymer polycarbonate, polycarbonate resin A, and methyl methacrylate-styrene-silicon core-shell copolymer are placed in a mixing pot in a ratio of 10:35:50:5, wherein the total mass fraction of octaphenylcyclotetrasiloxane, silicon copolymer polycarbonate, polycarbonate resin A, and methyl methacrylate-styrene-silicon core-shell copolymer is 100 parts, and 0.1 parts of hindered phenol antioxidant, 0.2 parts of phosphite antioxidant, and 0.3 parts of pentaerythritol stearate are added for blending.

[0180] (5) The mixed material prepared in step (4) is fed into a twin-screw extruder through a feeding hopper at a uniform speed, and melt-extruded and granulated in the twin-screw extruder to obtain a fluorine-free and halogen-free polycarbonate flame retardant masterbatch.

[0181] Embodiment 9:

[0182] The present embodiment provides a high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition, which is prepared from the following raw materials in parts by weight:

[0183]

[0184] The total weight of polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free flame retardant masterbatch is 100 parts.

[0185] The above-mentioned high impact fluorine-free and halogen-free flame retardant polycarbonate composition method, reference Figure 1 , including the following steps:

[0186] (4) The polycarbonate resin A, the polycarbonate resin B, and the fluorine-free and halogen-free polycarbonate flame retardant masterbatch were placed in a vacuum oven at 100° C. and dried for 4 hours.

[0187] (2) The polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free polycarbonate flame retardant masterbatch dried in step (1) are mixed, the speed of the mixing pot is 500 r / min, and the mixing time is 8 min.

[0188] (3) The hindered phenol antioxidant, the phosphite antioxidant and pentaerythritol stearate are mixed, the rotation speed of the mixing pot is 300 r / min, and the mixing time is 5 min.

[0189] (4) mixing the mixed material obtained in step (2) and the mixed material obtained in step (3); the rotating speed of the mixing pot is 500 r / min, and the mixing time is 10 min.

[0190] (5) adding the mixed material obtained in step (4) into a twin-screw extruder through a feeding hopper at a uniform speed, and performing melt extrusion and granulation in the twin-screw extruder. The process parameters of granulation include: a temperature of zone 1 of 230° C., a temperature of zone 2 of 235° C., a temperature of zone 3 of 240° C., a temperature of zone 4 of 245° C., a temperature of zone 5 of 250° C., a temperature of zone 6 of 250° C., a temperature of zone 7 of 250° C., a temperature of zone 8 of 245° C., a die head temperature of 265° C., and a screw speed of 500 rpm. The twin-screw extruder has a single-thread screw shape, a ratio of screw length L to diameter D of L / D of 35, and two meshing block areas and one reverse thread area are provided on the screw.

[0191] The preparation method of the fluorine-free and halogen-free polycarbonate flame retardant masterbatch used in Example 1 is as follows:

[0192] (1) In a three-necked flask equipped with a stirring device, a condenser and a thermometer, accurately weigh 150g of diphenyldimethoxysilane, 240g of acetone and 8g of deionized water, and then start the agitator until all the ingredients are fully mixed and evenly distributed. Next, dissolve 0.04g of NaOH in 16g of methanol, and after ensuring complete dissolution, slowly add this solution to the three-necked flask. Subsequently, raise the system temperature to 55 degrees Celsius, start the reflux device, and maintain this condition for 4 hours. After the reaction is completed, separate the product by suction filtration, wash it three times with anhydrous ethanol, and then wash it three times with deionized water until the filtrate is neutral. Finally, place the washed product in a vacuum dryer and dry it thoroughly to obtain white crystalline octaphenylcyclotetrasiloxane.

[0193] (2) The octaphenylcyclotetrasiloxane prepared in step (1) was placed in a vacuum oven at 80° C. and dried for 4 h.

[0194] (3) Place the silicon copolymer polycarbonate and polycarbonate resin A in a vacuum oven at 100° C. and dry for 4-6 hours.

[0195] (4) The octaphenylcyclotetrasiloxane dried in step (2) and step (3) and silicon copolymer polycarbonate, polycarbonate resin A, and methyl methacrylate-styrene-silicon core-shell copolymer are placed in a mixing pot in a ratio of 10:25:60:5, wherein the total mass fraction of octaphenylcyclotetrasiloxane, silicon copolymer polycarbonate, polycarbonate resin A, and methyl methacrylate-styrene-silicon core-shell copolymer is 100 parts, and 0.1 part of hindered phenol antioxidant, 0.2 part of phosphite antioxidant, and 0.3 part of pentaerythritol stearate are added for blending.

[0196] (5) The mixed material prepared in step (4) is fed into a twin-screw extruder through a feeding hopper at a uniform speed, and melt-extruded and granulated in the twin-screw extruder to obtain a fluorine-free and halogen-free polycarbonate flame retardant masterbatch.

[0197] Comparative Example 1:

[0198] The present embodiment provides a high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition, which is prepared from the following raw materials in parts by weight:

[0199]

[0200] The total weight of polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free flame retardant masterbatch is 100 parts.

[0201] The above-mentioned high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition method comprises the following steps:

[0202] (1) The polycarbonate resin A, the polycarbonate resin B, and the fluorine-free and halogen-free polycarbonate flame retardant masterbatch were placed in a vacuum oven at 100° C. and dried for 4 hours.

[0203] (2) The polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free polycarbonate flame retardant masterbatch dried in step (1) are mixed, the speed of the mixing pot is 500 r / min, and the mixing time is 8 min.

[0204] (3) The hindered phenol antioxidant, the phosphite antioxidant and pentaerythritol stearate are mixed, the rotation speed of the mixing pot is 500 r / min, and the mixing time is 8 min.

[0205] (4) mixing the mixed material obtained in step (2) and the mixed material obtained in step (3); the rotating speed of the mixing pot is 500 r / min, and the mixing time is 10 min.

[0206] (5) adding the mixed material obtained in step (4) into a twin-screw extruder through a feeding hopper at a uniform speed, and performing melt extrusion and granulation in the twin-screw extruder. The process parameters of granulation include: a temperature of zone 1 of 230° C., a temperature of zone 2 of 235° C., a temperature of zone 3 of 240° C., a temperature of zone 4 of 245° C., a temperature of zone 5 of 250° C., a temperature of zone 6 of 250° C., a temperature of zone 7 of 250° C., a temperature of zone 8 of 245° C., a die head temperature of 265° C., and a screw speed of 500 rpm. The twin-screw extruder has a single-thread screw shape, a ratio of screw length L to diameter D of L / D of 35, and two meshing block areas and one reverse thread area are provided on the screw.

[0207] Comparative Example 2:

[0208] The present embodiment provides a high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition, which is prepared from the following raw materials in parts by weight:

[0209]

[0210] The total weight of polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free flame retardant masterbatch is 100 parts.

[0211] The above-mentioned high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition method comprises the following steps:

[0212] (1) The polycarbonate resin A, the polycarbonate resin B, and the fluorine-free and halogen-free polycarbonate flame retardant masterbatch were placed in a vacuum oven at 100° C. and dried for 4 hours.

[0213] (2) The polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free polycarbonate flame retardant masterbatch dried in step (1) are mixed, the speed of the mixing pot is 500 r / min, and the mixing time is 8 min.

[0214] (3) The hindered phenol antioxidant, the phosphite antioxidant and pentaerythritol stearate are mixed, the rotation speed of the mixing pot is 500 r / min, and the mixing time is 8 min.

[0215] (4) mixing the mixed material obtained in step (2) and the mixed material obtained in step (3); the rotating speed of the mixing pot is 500 r / min, and the mixing time is 10 min.

[0216] (5) adding the mixed material obtained in step (4) into a twin-screw extruder through a feeding hopper at a uniform speed, and performing melt extrusion and granulation in the twin-screw extruder. The process parameters of granulation include: a temperature of zone 1 of 230° C., a temperature of zone 2 of 235° C., a temperature of zone 3 of 240° C., a temperature of zone 4 of 245° C., a temperature of zone 5 of 250° C., a temperature of zone 6 of 250° C., a temperature of zone 7 of 250° C., a temperature of zone 8 of 245° C., a die head temperature of 265° C., and a screw speed of 500 rpm. The twin-screw extruder has a single-thread screw shape, a ratio of screw length L to diameter D of L / D of 35, and two meshing block areas and one reverse thread area are provided on the screw.

[0217] The fluorine-free and halogen-free polycarbonate flame retardant masterbatch used in Comparative Example 2 is the same as that in Example 1.

[0218] Comparative Example 3:

[0219] The present embodiment provides a high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition, which is prepared from the following raw materials in parts by weight:

[0220]

[0221]

[0222] The total weight of polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free flame retardant masterbatch is 100 parts.

[0223] The above-mentioned high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition method comprises the following steps:

[0224] (1) The polycarbonate resin A, the polycarbonate resin B, and the fluorine-free and halogen-free polycarbonate flame retardant masterbatch were placed in a vacuum oven at 100° C. and dried for 4 hours.

[0225] (2) The polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free polycarbonate flame retardant masterbatch dried in step (1) are mixed, the speed of the mixing pot is 500 r / min, and the mixing time is 8 min.

[0226] (3) The hindered phenol antioxidant, the phosphite antioxidant and pentaerythritol stearate are mixed, the rotation speed of the mixing pot is 500 r / min, and the mixing time is 8 min.

[0227] (4) mixing the mixed material obtained in step (2) and the mixed material obtained in step (3); the rotating speed of the mixing pot is 500 r / min, and the mixing time is 10 min.

[0228] (5) adding the mixed material obtained in step (4) into a twin-screw extruder through a feeding hopper at a uniform speed, and performing melt extrusion and granulation in the twin-screw extruder. The process parameters of granulation include: a temperature of zone 1 of 230° C., a temperature of zone 2 of 235° C., a temperature of zone 3 of 240° C., a temperature of zone 4 of 245° C., a temperature of zone 5 of 250° C., a temperature of zone 6 of 250° C., a temperature of zone 7 of 250° C., a temperature of zone 8 of 245° C., a die head temperature of 265° C., and a screw speed of 500 rpm. The twin-screw extruder has a single-thread screw shape, a ratio of screw length L to diameter D of L / D of 35, and two meshing block areas and one reverse thread area are provided on the screw.

[0229] The fluorine-free and halogen-free polycarbonate flame retardant masterbatch used in Comparative Example 3 is the same as that in Example 1.

[0230] Comparative Example 4:

[0231] Comparative Example 4 is used as a reference with Example 1.

[0232] The comparative example is compared with Example 1, except that the ratio of octaphenylcyclotetrasiloxane, silicon copolymer polycarbonate, polycarbonate resin A, and methyl methacrylate-styrene-silicone core-shell copolymer in the fluorine-free and halogen-free polycarbonate flame retardant masterbatch is 0:35:60:5, and the other processes are the same as Example 1.

[0233] Comparative Example 5:

[0234] Comparative Example 5 is used as a reference with Example 1.

[0235] The comparative example is compared with Example 1, except that the ratio of octaphenylcyclotetrasiloxane, silicon copolymer polycarbonate, polycarbonate resin A, and methyl methacrylate-styrene-silicone core-shell copolymer in the fluorine-free and halogen-free polycarbonate flame retardant masterbatch is 20:35:45:0, and the other processes are the same as Example 1.

[0236] Comparative Example 6

[0237] Comparative Example 6 is used as a reference with Example 1.

[0238] The comparative example is compared with Example 1, except that the ratio of octaphenylcyclotetrasiloxane, silicon copolymer polycarbonate, polycarbonate resin A, and methyl methacrylate-styrene-silicone core-shell copolymer in the fluorine-free and halogen-free polycarbonate flame retardant masterbatch is 20:0:75:5, and the other processes are the same as Example 1.

[0239] Performance testing and results

[0240] The high-impact fluorine-free and halogen-free flame-retardant polycarbonate compositions prepared in the above examples and comparative examples were subjected to the following performance tests:

[0241] Impact performance: tested according to ASTM D256-10 standard, the specimen thickness is 3.27mm, the higher the value, the better;

[0242] Bending strength: tested according to ASTM D790-10 standard, the specimen thickness is 3.27mm, the higher the value, the better;

[0243] Tensile properties: tested according to ASTM D638-14 standard, the thickness of the specimen is 3.27mm, the width of the narrow part is 12.67mm, the higher the value, the better;

[0244] Melt index: tested according to ASTM D1238-13 standard, test temperature is 300℃, load is 1.2kg;

[0245] Flame retardant performance: tested according to UL-94 standard, the specimen thickness is 1.6mm, and the shorter the total burning time of T1+T2 of the 5 test samples, the better the flame retardant performance.

[0246] The performance test results are shown in Table 1:

[0247] Table 1 Performance of fluorine-free and halogen-free flame-retardant polycarbonate compositions of Examples and Comparative Examples

[0248]

[0249]

[0250] Embodiment 1-6 is to adjust the addition amount of polycarbonate A, polycarbonate B, fluorine-free and halogen-free polycarbonate flame retardant masterbatch. It can be seen from the data in the observation table that with the increase of the content of fluorine-free and halogen-free polycarbonate flame retardant masterbatch, its flame retardant performance is significantly improved, but the notched impact strength decreases, the melt index then shows an upward trend, and the melt strength decreases. When embodiment 5 is burned, the strip shows a dripping trend, and the flame retardant performance is not significantly improved. This phenomenon can be attributed to the small amount of silanols remaining in octaphenylcyclotetrasiloxane. This substance can cause slight degradation of polycarbonate resin in the process of co-extrusion with polycarbonate resin, resulting in shortening of molecular chain length, and the degree of entanglement between molecular chains is slightly weakened. At the same time, octaphenylcyclotetrasiloxane is dispersed in polycarbonate resin as a stress concentration point, and the tensile strength of polycarbonate resin can also be reduced. Therefore, with the increase of the amount of fluorine-free and halogen-free polycarbonate flame retardant masterbatch, the mechanical properties and melt strength of the material decrease, and the processing performance is slightly improved. Nevertheless, the polycarbonate compositions of Examples 1 to 6 still maintain excellent mechanical properties and flame retardant properties. By comprehensively analyzing the performance data of the polycarbonate compositions prepared in Examples 1 to 6, it can be concluded that the polycarbonate composition prepared in Example 1 has the best comprehensive performance and its raw material ratio is also the best.

[0251] Examples 7-9 are for adjusting the content of each component in the fluorine-free and halogen-free polycarbonate flame retardant masterbatch. It can be seen from the data that the basic mechanical properties and flame retardant properties of the polycarbonate composition prepared by adjusting the content of each component in the fluorine-free and halogen-free polycarbonate flame retardant masterbatch within a reasonable range are still excellent, and different application scenarios can be adapted by adjusting the content of each component in the fluorine-free and halogen-free polycarbonate flame retardant masterbatch.

[0252] Compared with Comparative Example 1, in Comparative Example 1, no fluorine-free and halogen-free polycarbonate flame retardant masterbatch was added, and the impact strength of the obtained polycarbonate composition was improved, and the tensile strength and flexural strength were also improved. Although the flame retardant grade of polycarbonate itself is V-2, the polycarbonate composition in Comparative Example 1 has a dripping phenomenon. This is because no corresponding anti-dripping agent is added, and the melt strength is insufficient. In Example 1, fluorine-free and halogen-free polycarbonate flame retardant masterbatch is added, which contains a silicon-based core-shell structure coating toughening agent of high molecular weight silicon copolymer polycarbonate and methyl methacrylate-styrene-organic silicon copolymer, so that the average molecular weight of the polycarbonate composition prepared in Example 1 is greater than that of the polycarbonate composition prepared in Comparative Example 1. Although the melt index of Example 1 is larger than that of Comparative Example 1 in macroscopic terms, the polycarbonate composition prepared in Example 1 contains octaphenylcyclotetrasiloxane, and the negative impact of the mechanical properties brought by octaphenylcyclotetrasiloxane is offset by the toughening synergistic effect of the silicon copolymer polycarbonate and the methyl methacrylate-styrene-silicone copolymer, thereby ensuring sufficient melt strength and excellent flame retardant properties.

[0253] Compared with Example 2, in Example 2, since no polycarbonate B is added, the impact strength of the obtained polycarbonate composition is significantly reduced, the total combustion time is slightly prolonged, the melt index of the material is increased, and obvious dripping phenomenon is shown during the combustion process. This shows that the polycarbonate resin B in the present invention plays an irreplaceable role in improving the molecular weight of the polycarbonate composition, and from a macroscopic perspective, it helps to enhance the overall impact strength and melt strength of the material.

[0254] Compared with Example 3, in Example 3, since polycarbonate A is not added, the impact strength of the prepared polycarbonate composition is improved, and the flame retardant performance is also slightly improved, but the melt index of the material is significantly reduced, which will lead to poor processing performance and increased loss during processing. This shows that polycarbonate resin A plays an irreplaceable role in adjusting the molecular weight of the polycarbonate composition in the present invention. From a macroscopic perspective, it helps to balance the molecular weight of the polycarbonate composition so that it can achieve a suitable melt strength and have good processing performance.

[0255] Compared with Comparative Example 4, in Example 1, octaphenylcyclotetrasiloxane was not added to the fluorine-free and halogen-free polycarbonate flame retardant masterbatch in Comparative Example 4, but polycarbonate A and polycarbonate B were melt-blended together to prepare the produced polycarbonate mixture, and the impact strength of the produced polycarbonate mixture was improved, but its flame retardant performance failed to reach the V0 level specified in UL-94. This shows that the octaphenylcyclotetrasiloxane contained in the fluorine-free and halogen-free polycarbonate flame retardant masterbatch in the present invention is crucial and indispensable for improving the flame retardant performance of the polycarbonate mixture.

[0256] Compared with Comparative Example 5, in Example 1, methyl methacrylate-styrene-silicone core-shell copolymer is not added to the fluorine-free and halogen-free polycarbonate flame retardant masterbatch in Comparative Example 5. Although the flame retardant properties of the produced polycarbonate mixture are improved, its impact strength is greatly reduced. This is because methyl methacrylate-styrene-silicone copolymer belongs to a silicon-based core-shell structure encapsulating toughening agent. Its addition will reduce the thermal shear force of the material. The molecular chain segments will not be significantly reduced in the overall molecular weight of the protected material during the extrusion process, thereby improving the impact properties of the material. However, since its component is rubber, it has the characteristic of being easy to burn, which reduces the overall flame retardant effect of the material. The macroscopic performance is that the toughness of the material obtained by the embodiment 1 scheme is greatly improved, and the flame retardant effect and material fluidity are slightly reduced. This shows that the methyl methacrylate-styrene-silicone copolymer contained in the fluorine-free and halogen-free polycarbonate flame retardant masterbatch in the present invention is very important for improving the toughness of the polycarbonate mixture.

[0257] Compared with Example 6, in Example 1, no silicon copolymer polycarbonate is added to the fluorine-free and halogen-free polycarbonate flame retardant masterbatch in Example 6, so that the fluidity of the polycarbonate composition prepared in Example 6 is slightly improved, but the impact strength and flame retardant properties are reduced. This is because the silicon copolymer polycarbonate in the composition can increase the degree of entanglement between molecular chains, reduce the slippage between molecular chains, make the molecular chains closer, and have higher impact resistance. The macroscopic manifestation is decreased fluidity, increased melt strength and increased impact strength of the composition. Moreover, with the addition of organic silicon groups in silicon copolymer polycarbonate, the carbonization efficiency of the composition is faster during combustion, and the burning time is significantly reduced. This shows that the silicon copolymer polycarbonate contained in the fluorine-free and halogen-free polycarbonate flame retardant masterbatch in the present invention is indispensable for improving the toughness and flame retardant properties of the polycarbonate mixture.

[0258] By comparison, it can be found that the fluorine-free and halogen-free flame-retardant polycarbonate composition prepared by using the raw materials of the present invention has excellent mechanical properties, flame retardant properties and processing properties, and the formula components are simple. The biggest advantage is that it is absolutely fluorine-free and halogen-free, and will not be restricted by relevant policies. It can be applied to materials fields such as home appliances and consumer electronics.

[0259] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0260] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A high impact fluorine-free and halogen-free flame retardant polycarbonate composition, characterized in that: The invention comprises the following raw materials in parts by weight: The total weight percentage of polycarbonate resin A, polycarbonate resin B and fluorine-free and halogen-free polycarbonate flame retardant masterbatch is 100 parts; the fluorine-free and halogen-free polycarbonate flame retardant masterbatch comprises the following components: octaphenylcyclotetrasiloxane, silicon copolymer polycarbonate, polycarbonate resin A and methyl methacrylate-styrene-silicone core-shell copolymer.

2. The high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition according to claim 1, characterized in that: The melt index of the polycarbonate resin A at 300° C. / 1.2 kg is 8-12 g / 10 min.

3. The high impact fluorine-free and halogen-free flame retardant polycarbonate composition according to claim 1, characterized in that: The polycarbonate resin B has a melt index of 2-4 g / 10 min at 300° C. / 1.2 kg.

4. The high impact fluorine-free and halogen-free flame retardant polycarbonate composition according to claim 1, characterized in that: The fluorine-free and halogen-free polycarbonate flame retardant masterbatch further comprises a hindered phenol antioxidant, a phosphite antioxidant and pentaerythritol stearate.

5. The high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition according to claim 4, characterized in that: The preparation method of the fluorine-free and halogen-free polycarbonate flame retardant masterbatch is as follows: The dried octaphenylcyclotetrasiloxane, silicon copolymer polycarbonate, polycarbonate resin A and methyl methacrylate-styrene-silicone core-shell copolymer are uniformly mixed, and a hindered phenol antioxidant, a phosphite antioxidant and pentaerythritol stearate are added for blending to obtain a mixture; the mixture is added into a twin-screw extruder, and melt-extruded and granulated in the twin-screw extruder to obtain a fluorine-free and halogen-free polycarbonate flame retardant masterbatch.

6. The high impact fluorine-free and halogen-free flame retardant polycarbonate composition according to claim 4, characterized in that: The melting index of the silicon copolymer polycarbonate at 300° C. / 1.2 kg is 2-4 g / 10 min, and the melting index of the polycarbonate resin A at 300° C. / 1.2 kg is 8-12 g / 10 min.

7. The high impact fluorine-free and halogen-free flame retardant polycarbonate composition according to claim 1, characterized in that: The hindered phenol antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol, and the phosphite antioxidant is bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphate.

8. The method for preparing a high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition according to any one of claims 1 to 7, characterized in that: The following steps are involved: Polycarbonate resin A, polycarbonate resin B, fluorine-free and halogen-free polycarbonate flame retardant masterbatch, hindered phenol antioxidant, phosphite antioxidant and pentaerythritol stearate are uniformly mixed to obtain a mixture; the mixture is added into a twin-screw extruder, and melt-extruded and granulated in the twin-screw extruder to obtain a high-impact fluorine-free and halogen-free flame retardant polycarbonate composition.

9. The method for preparing a high-impact fluorine-free and halogen-free flame-retardant polycarbonate composition according to claim 8, characterized in that: The temperatures of each zone in the twin-screw extruder are: zone one temperature is 220-240°C, zone two temperature is 225-255°C, zone three temperature is 230-260°C, zone four temperature is 225-260°C, zone five temperature is 225-260°C, zone six temperature is 225-260°C, zone seven temperature is 225-260°C, zone eight temperature is 225-260°C, the die head temperature of the twin-screw extruder is 250-270°C, and the screw speed is 300-600rpm.

10. The high impact fluorine-free and halogen-free flame retardant polycarbonate composition according to any one of claims 1 to 7 is used in the field of home appliances or consumer electronics.

Citation Information

Patent Citations

  • Low-internal-stress fluoride-free flame-retardant polycarbonate material and preparation method thereof

    CN117511167A